2010
DOI: 10.1093/carcin/bgq029
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of macrophage inflammatory protein 1α (MIP1α) in promotion of rat lung and mammary carcinogenic activity of nanoscale titanium dioxide particles administered by intra-pulmonary spraying

Abstract: Titanium dioxide (TiO(2)) is evaluated by World Health Organization/International Agency for Research on Cancer as a Group 2B carcinogen. The present study was conducted to detect carcinogenic activity of nanoscale TiO(2) administered by a novel intrapulmonary spraying (IPS)-initiation-promotion protocol in the rat lung. Female human c-Ha-ras proto-oncogene transgenic rat (Hras128) transgenic rats were treated first with N-nitrosobis(2-hydroxypropyl)amine (DHPN) in the drinking water and then with TiO(2) (ruti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 44 publications
3
32
1
Order By: Relevance
“…Intrapulmonary spraying has been shown to be an efficient method to deliver particle materials deep into the lung. (20)(21)(22)(23)(24) Our results demonstrated that MWCNT, like asbestos, translocated from the lung into the pleural cavity and induced inflammatory responses in the pleural cavity and, importantly, hyperplastic visceral mesothelial proliferation. These findings are important in understanding whether MWCNT have the potential to cause asbestos-like pleural lesions.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…Intrapulmonary spraying has been shown to be an efficient method to deliver particle materials deep into the lung. (20)(21)(22)(23)(24) Our results demonstrated that MWCNT, like asbestos, translocated from the lung into the pleural cavity and induced inflammatory responses in the pleural cavity and, importantly, hyperplastic visceral mesothelial proliferation. These findings are important in understanding whether MWCNT have the potential to cause asbestos-like pleural lesions.…”
mentioning
confidence: 64%
“…(38) Previously, we used a total dose of 1.25 mg/rat of titanium dioxide over a 9-day period and identified factors involved in titanium dioxide-induced lung lesions. (24) In the present study, we used the same protocol for the purpose of induction of observable pleural lesions and inflammation in the pleural cavity as well to ensure the presence of a detectable number of fibers in the pleural cavity after short-term administration; this dose was higher than the NIOSH exposure limit. Time-and dose-dependent experiments are needed in future studies, and further investigation is also required to elucidate cytokines and other factors that cause parietal mesothelial proliferation in animal models that are more relevant to humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also shown that carbon black nanoparticles (9)(10)(11), titanium dioxide nanoparticles (12), and carbon nanotubes (13,14) can promote allergic sensitization, allergic airway inflammation (AAI), and/or stimulate dendritic cell (DC) and allergen-specific T cells. However, a significant component of these particle adjuvant effects has been attributed to adsorbed toxic chemicals and metallic impurities and the ability to induce oxidative stress (6,7,13,(15)(16)(17)(18)(19). Notably, information regarding the long-term effects of inert, nontoxic and noninflammatory nanoparticles delivered into the lung on asthma development and pulmonary DC distribution and function is lacking.…”
mentioning
confidence: 99%